Utilization of macro encapsulated phase change materials for the development of thermal energy storage and structural lightweight aggregate concrete. (1st February 2015) - Memon, Shazim Ali; Cui, H.Z.; Zhang, Hang; Xing, Feng
Highlights: Compressive strength of LWAC with Paraffin–LWA was higher than 15 MPa. Shrinkage strain with Paraffin–LWA reduced by 41.8%. For outdoor testing, temperature at room center with Paraffin–LWA reduced by 2.9 °C. Recovery period with Paraffin–LWA was less than average life span of building. A reduction of 465 kg CO2 -eq/year or 12.91 kg CO2 -eq/year/m 2 was achieved. Abstract: Structural–functional integrated materials are one of directions of rapid development for saving-energy materials. Phase Change Materials (PCMs) are latent thermal storage materials possessing a large amount of heat energy stored during its phase change stage. Porous lightweight aggregate (LWA) can serve as the carrier for PCM. In this research, a structural concrete with function of indoor temperature control were prepared by using macro encapsulated PCM–LWA. The indoor and outdoor tests were performed to determine the thermal performance of the lightweight aggregate concrete (LWAC) containing macro encapsulated Paraffin–LWA. The compressive strength and shrinkage strain of LWAC with macro encapsulated PCM–LWA were evaluated. Finally, the economic and environmental aspects of application of macro encapsulated Paraffin–LWA in a typical floor area of public housing rental flat in Hong Kong were assessed. From indoor thermal performance test, it was found that LWAC incorporated with macro encapsulated Paraffin–LWA has a function of reducing the energy consumption by decreasing the indoor temperature; flatten the fluctuation of indoor temperature and shifting the loads away from the peak periods. Moreover, from outdoor thermal performance test, it was found that the performance of macro encapsulated Paraffin–LWA in adjusting the room temperature was optimized when there was a remarkable temperature difference between the day and night. Test results showed that the compressive strengths of LWAC incorporating macro encapsulated Paraffin–LWA at 28 days was higher than control LWAC (without macro encapsulated Paraffin–LWA) and was found to be over 15 MPa. The shrinkage strain reduced with the incorporation of macro encapsulated Paraffin–LWA in LWAC and therefore has a beneficial effect on the volume stability of LWAC. From simple economic evaluation of macro encapsulated Paraffin–LWA in a typical floor area of public housing rental flat in Hong Kong, the recovery or payback period was found to be less than the average life span of a residential building in Hong Kong. Therefore, incorporation of macro encapsulated Paraffin–LWA in LWAC building walls is economically feasible. Finally, from environmental prospect, a reduction of 465 kg CO2 -eq/year or 12.91 kg CO2 -eq/year/m 2 was achieved. This reduction would contribute to mitigate Greenhouse Gases emissions over the life span of building. It can therefore be concluded that the developed macro encapsulated PCM LWAC can be used for thermal and structural applications in buildings.